PERAN PARTISIPASI ANGGOTA LEGISLATIF PEREMPUAN DALAM PENGAMBILAN KEPUTUSAN DI LEMBAGA DPRD KOTA SEMARANG PERIODE 2009-2014 - Gesmy Anita Sitanggang; Nur Hidayat Sardini; Purwoko . (Journal of Politic and Government Studies, 2015)
Abstract:Plunging women into the political sphere demanding their active role in every activity in parliament. Similarly, women legislators in Parliament Semarang period of 2009-2014, they have roles and responsibilities as representatives of the people that prosper and giving a voice to the people especially those for the benefit of the group. Researchers using descriptive research method with qualitative approach, and using the method of collecting evidence through in-depth interviews, documentation, observation and triangulation. The results showed that the role of women in decision-making in Semarang City Council in the 2009-2014 period were minimal. Most of them admitted that in each meeting, the women do not dare to propose opinion or disagrees with male legislators. This because of lack of confidence and quality of women's knowledge politic itself. It can be said that women's participation in influencing a decision is passive. This was confirmed on the results of interviews which states that in every meeting women just attend and listen to the proceedings.Keywords : The Role of Women Legislators, Women Participation, Decision Making